Biostratigraphy of Yamama Formation in Faihaa Oil Field, Southern Iraq - Al-Hassani, Maryam; Al-Dulaimi, Salam (Iraqi Journal of Science, 2021)
The Yamama Formation was studied in three wells (Fh-1, Fh-2, and Fh-3) within Faihaa oil field, south Iraq. Thin sections were studied by using the polarizing microscope examination in order to determine microfossils and biozone. Thirty-five species of benthic foraminifera were recognized, including four index species. In addition, twelve species of calcareous green algae were recognized, including two index species. Other fossils that were recognized in Yamama Formation include Gastropoda, Bryozoa, Coral, Rudist, and Pelecypoda. Six biozones were observed, which are Charentia cuvillieri sp. (Range Zone of Berriasian age), Psudochryalidina infracretacea sp. (Range Zone of Berriasian age), Pseudocyclammina Lituus sp. (Range Zone of Valanginian age), Nezzazata Perforate sp.andChoffatella sp.(Assemblage Zoneof Berriasian-Valanginian age), Desycladales Green Algae- Cylindroporella sp. (Range Zone of Early Cretaceous- Berriasian age), and Desycladales Green Algae- Salpingoporella cf. circassa sp. (Range Zone of Valanginian age). According to these biozones, the age of Yamama Formation was distinguished to be the Berriasian-Valanginian.